Inclusive strategies: attention to diverse students in primary education, the experience of Honduran teachers (Innovaciones Educativas, 2022)
The manuscript presents experiences in teaching-learning strategies and methodologies of Honduran academic teaching staff in the educational inclusion of children with special educational needs. The analysis unit consisted of ten people who had experience in inclusion at the primary and basic educational levels. The approach was qualitative, through a phenomenological type design; the instruments used to obtain the information were two: first, the narrative interview, and second, a focus group. We applied a script of eleven questions in the interview and ten in the focus group. The results allowed us to understand that cooperative and participatory strategies stand out to harmonize their skills and social relationships in the classroom. Albeit there is no solid training in this area, creative and inventive skills were used to configure inclusive environments. In conclusion, the supports for the attention to diversity are minuscule. It is suggested to carry out other studies related to the aids granted in the educational establishments to improve skills regarding attention to diversity.
Keywords: Primary education; inclusive education; educational strategies; special educational needs; academic teaching staff; education